Beverage preference (coffee vs. tea) according to CYP1A2 gene rs2470893 SNP genotypes in the Tunisian population - Denden, Sabri (2023)
Caffeine intake has been positively or negatively associated with the risk of chronic disease. Genome-wide association studies identified single-nucleotide polymorphisms (rs2472297 and rs2470893) in Cytochrome P450 1A2 (CYP1A2) gene that are involved in habitual caffeine intake. In this study, we investigated the association of common CYP1A2 SNPs (rs762551, rs2472297 and rs2470893) with most consumed caffeinated beverages intake (coffee and tea) in the Tunisian population. Five hundred and twenty healthy blood donors were enrolled. Coffee and tea intake data were extracted from dietary questionnaires of the participants. Genotyping was performed using PCR–RFLP. p < 0.05 was considered as statistically significant.